Planning of low-cost 77-GHz radar transceivers for automotive applications - Ameri Mahabadi, H.; Attaran, A.; Moghavvemi, M. (2012)
The key to prevent driving accidents by automotive radar systems at high speed is to have optimum and accurate estimation of position representation and fast visualization of the environment.